Application of interpretative phenomenological analysis (IPA) in studying the intercultural experience of learning jazz improvisation - Chan, Cheong Jan; Wong, Siao Ern (Universiti Putra Malaysia Press, 2016)
Jazz studies and tertiary education in music are a “new culture” to Southeast Asian countries, however common they may appear to be. Low readiness for learning, knowledge and skill gap, lack of appreciation of subject learned, low self esteem, and unrefined pedagogy have been commonplace in music colleges in the past two decades in Malaysia. The need to examine and support the local students’ jouney into the intercultural process of professional music training in a still developing music-social environment is urgent. Using Søren Kierkegaard’s (year?) notion on subjectivity as a base, an application of Jonathan Smith style IPA were utilised to study the learning process of jazz major tertiary students in a Southeast Asian country. This paper elaborated the concepts and considerations made in the construct of this new methodological application with some early results obtained from the semi structured interview. Anything perceived within an individual was found to influence or determine by the particularity of the individual’s background, and the perception of the object also cultivated an understanding of self. From these, the three parts of the methodological frame of phenomenology were laid, which were the object (which was the subject of study, i.e., jazz), Perceptions (the way the object was being grasped by the learners), and Self-image (the understanding of self, the evaluative aspect). The result revealed the student’s particular views on the meaning of being a student, and her basis for value judgement and decision making along the learning process, which were insights that may enable a connection into her prior experiences and an explanation of the present outlook of her learning problems.